My Sense of Silence : Memoirs of a Childhood with Deafness - Davis, Lennard J., 1949- (Book collections on Project MUSE., 2000)
"Lennard J. Davis grew up as the hearing child of deaf parents. In this candid, affecting, and often funny memoir, he recalls the joys and confusions of this special world, especially his complex and sometimes difficult relationships with his working-class Jewish immigrant parents." "Growing up in a crowded one-bedroom South Bronx tenement, Lennard felt himself "a hearing outsider" caught between two worlds. Davis recounts childhood loneliness and fear, adolescent frustration compounded by embarrassment at his parents' deafness, and intellectual aspirations that ran counter to their compliant stoicism. He vividly describes his father's devotion to race walking and to televised baseball games, a trip to England with his mother on the Queen Elizabeth, and his successful efforts to relocate his family to a better apartment. He also recounts his problematic relationship with his elder brother, whom he both idolized and feared, and his college years at Columbia University, where (to his parents' chagrin) he participated in the historic campus demonstrations of May 1968." "In a moving epilogue, Davis tells of his adult involvement with CODA (Children of Deaf Adults) and of coming to terms with a surprising realization. "Though I was hearing," he says, "deafness was in me.""--Jacket.